A damage coupled elastic-plastic constitutive model and its application on low cycle fatigue life prediction of turbine blade. (February 2020) - Guo, Zixu; Huang, Dawei; Yan, Xiaojun; Zhang, Xiaoyong; Qi, Mingjing; Fan, Jun
Highlights: The damage variable is coupled with multilinear elastic-plastic constitutive model. High-precision numerical method is employed in continuum damage mechanics model. The convergence of the proposed model is examined. To validate the model, LCF experiments are conducted on turbine blades. Abstract: Based on continuum damage mechanics (CDM), a damage coupled elastic-plastic constitutive model combined with multilinear hardening relation is proposed and applied on low cycle fatigue (LCF) life prediction of turbine blade. The model has considered the local rigidity attenuation of structure caused by fatigue damage in elastic and plastic stage, and it is implemented combining with finite element method (FEM) to predict the crack initiation lives of turbine blades. Runge-Kutta (RK) method is employed in the solving process of damage accumulation. By conducting the calculation in several time step sizes, the convergence of the proposed model is examined. To validate the predicted results, groups of LCF experiments are conducted on full-scale turbine blades. The macroscopic fracture shows that the crack initiation region is in accordance with the predicted results. Compared with the experimental results, the predicted lives of the proposed model, an existing CDM model without coupling with constitutive relation and Morrow model are within factors of 2.31, 3.93 and 9.15 in scatter band respectively, indicating the high accuracy of the proposed model. Expect for turbine blades, the proposed model can be used to predict the LCF lives of other structures.